2023
DOI: 10.1186/s13018-022-03470-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on the treatment of postmenopausal osteoporosis with quercetin in Liuwei Dihuang Pill based on network pharmacology

Abstract: Background Liuwei Dihuang Pill (LP) was verified to alleviate postmenopausal osteoporosis (PMOP) development. Nevertheless, the major constituent of LP and the related network pharmacology study remain unexplored. Methods Protein–protein interaction was established to identify the downstream target of LP in PMOP, and the related signaling pathway was investigated by bioinformatics analysis. MC3T3-E1 cells were added to ferric ammonium citrate (FAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…[34] However, the current in vitro research mainly focuses on the prevention and potential mechanism of quercetin on PMO. [35] For the first time, we demonstrated the role of quercetin in PMO through the mining of drug components, construction of network targets and molecular docking verification, which well corroborated previous views and provided a good reference for the next in vivo research or clinical trials of quercetin in the treatment of PMO. With regard to the effect of kaempferol on PMO, only studies have shown that kaempferol has an inhibitory effect on bone loss in rats with osteoporosis after ovariectomy, [36] but there is still no study on its potential mechanism and clinical effect.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[34] However, the current in vitro research mainly focuses on the prevention and potential mechanism of quercetin on PMO. [35] For the first time, we demonstrated the role of quercetin in PMO through the mining of drug components, construction of network targets and molecular docking verification, which well corroborated previous views and provided a good reference for the next in vivo research or clinical trials of quercetin in the treatment of PMO. With regard to the effect of kaempferol on PMO, only studies have shown that kaempferol has an inhibitory effect on bone loss in rats with osteoporosis after ovariectomy, [36] but there is still no study on its potential mechanism and clinical effect.…”
Section: Discussionsupporting
confidence: 84%
“…[51,52] Furthermore, AKT and PI3K are generally downregulated when osteoporosis occurs, illustrating that the progression of osteoporosis might be associated with cell injury. [35,53,54] There are many other studies on the role of PI3K/AKT pathway in PMO, for example, silence of miR-483-5p can alleviate postmenopausal osteoporosis through PI3K/AKT pathway [55] ; Chlorogenic acid can prevent osteoporosis in ovariectomized rats through PI3K/Akt pathway. [56] Therefore, PI3K/AKT pathway is an important pathway for the occurrence and development mechanism of PMO, and also an important medium for the treatment of PMO.…”
Section: Discussionmentioning
confidence: 99%
“…Que can reduce FAC-induced apoptosis and reactive oxygen species (ROS) production, downregulate the expression of caspase-3 and Bax, and upregulate the expression of Bcl-2 ( Xiao et al, 2023 ; Zhu et al, 2023 ). Que can attenuate chondrocyte apoptosis by modulating the Bcl-2/Bax-caspase-3 signaling pathway to reduce sodium nitroprusside-induced overproduction of intracellular ROS and restore mitochondrial membrane potential ( Hu et al, 2019 ).…”
Section: Molecular Mechanisms Of Que In Opmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is extensively used in China to treat various ailments, including OP. Liuwei Dihuang pills (LWDH pills) are a formulated medicine composed of six herbal ingredients: prepared Rehmannia root, Cornus officinalis , Cortex Moutan , Rhizoma Dioscoreae , Poria cocos , and Alismatis Rhizoma [ 10 ]. These herbal ingredients have been extensively recognized to confer therapeutic properties in TCM that include nourishing yin, tonifying the kidneys, replenishing the essence, and benefiting the marrow; in other words, they can promote the balance and stability of the human body’s internal environment and enhance the activity of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%